Questioning as advice resistance: writing tutorial interactions with L2 writers. Issue 3 (2nd September 2017) - Park, Innhwa
Abstract: While much research on writing tutorial interactions with second language (L2) writers has focused on the tutor's instructional practices, little attention has been given to the ways in which the tutee responds to them. Based on 6 h of video-recordings from 8 tutoring sessions between 6 tutors (L1 users of English) and 8 tutees (L2 users of English), this conversation analytic study examines how L2 writers resist their tutors' advice. In particular, the study focuses on the tutee's use of questioning as advice resistance and specifies two questioning practices: (1) asking a reversed polarity question and (2) proposing an alternative candidate revision. The analyses show that the tutee's advice-resisting question initiates the expansion of the sequence and affords the participants an opportunity to discuss the rationale behind the advice, revise the advice, or adopt the alternative way of revision. Overall, the present study adds to the existing body of research on L2 writing tutorial interactions by investigating an interactional practice of advice resistance and by showing various ways in which the participants engage in doing pedagogy as they co-construct the advice that reflects the tutee's knowledge and concern in the given moment.